Spatial characteristics of access of third-country citizens to the Hungarian public health care system - Illés, Sándor; Gellér-LukácsÉva (Hungarian Geographical Bulletin, 2016)
The effect of international migration on public health care system is one of the emerging themes within health and mobility studies. Unfortunately, there is scarce information on health situation of international migrants in Central and Eastern Europe. This research paper tries to contribute filling in this gap with a case study related to Hungary and it deals with the access and participation of third-country nationals to the Hungarian public health care system as patients. The study integrates quantitative and qualitative methodologies coupled with a holistic approach. Macro data of the National Health Insurance Fund was analysed and field works in the National Ambulance Service and at the Semmelweis University (Budapest) were carried out. The volumes and rates of nationals of Ukraine, China, Vietnam, Serbia, former Yugoslavia, Russia and Mongolia are the dominant groups in the provision of acute care, in-patient care, out-patient care, dental care and cash benefits. Acute care is relatively the most populous and medical treatments in capital institutions as opposed to countryside ones. The main spatial factors aff ecting the provider and supplier side of public health care system in Hungary are identified while concluding that third-country migrants utilize selectively the institutions of the Hungarian public health care system. Conclusions subscribe to the need for future research in this theme in the light of most recent international mobility upheavals.